Antidepressant Use in Siblings of Children With Cancer: A Danish Population-Based Cohort Study - Lund, Lasse Wegener (JNCI Cancer Spectr, 2020)
Siblings of children with cancer experience severe stress early in life. Most studies of mental health problems in these siblings are limited by being small, cross-sectional, or self-reporting. In a population-based cohort study, we investigated the risk for antidepressant use by linking several nationwide, population-based registries comparing 6644 siblings of children diagnosed with cancer from 1991-2009 with 128 436 population-based sibling comparisons using the Cox proportional hazards model. Irrespective of cancer type, no increased risk of antidepressant use in siblings of children with cancer was found (hazard ratio = 1.00, 95% confidence interval = 0.91 to 1.11). However, data suggested that siblings being young at cancer diagnosis had an increased risk (2-sided P(trend) = .01). Interaction analyses showed no modifying effect of parental socioeconomic position or antidepressant use. Findings from this study with a very low risk of bias are reassuring and important for families facing childhood cancer and for clinicians counseling these families.